Utilization of adsorption technique in the development of oral delivery system of lipid based nanoparticles - Chakraborty S.; Shukla D.; Vuddanda P.R.; Mishra B.; Singh S. (My University, 2025)
The objective of the present study was to employ suitable adsorbent with free flowing characteristics for improving the stability and physical properties of solid lipid nanoparticles (SLN) for oral administration. Stearic acid based nanoparticles of carvedilol phosphate were fabricated by solvent emulsification evaporation technique in sodium taurocholate solution prepared in pH 7.2 buffers (I-KH2PO4/NaOH or II-NaH2PO4/Na2HPO4) with 1% polyvinyl alcohol. Nanoparticles were then adsorbed by passing the nanodispersion through a Neusilin US2 (adsorbent) column. Interestingly, scanning electron microscopy revealed round deformed and even collapsed nanoparticles in Buffer-I and discrete spherical to ellipsoidal nanoparticles in Buffer-II which indicates the inability of nanoemulsion to crystallize and form SLN in Buffer-I. The successful formation of SLN in Buffer-II was confirmed by differential scanning calorimetry and X-ray diffraction. The retention of SLN from the nanodispersion by adsorption on the adsorbent imparted good flow property and resulted in a marked stability improvement of the formulation in terms of drug retention efficiency and release profile as compared to the simple nanosuspension. In conclusion, the adsorbent technology would be instrumental in imparting additional features to the existing conventional colloidal system for pharmaceutical application which would ease the process of capsule filling at industrial scale, simplify the handling of formulations by patients and can significantly improve the shelf life of the product for a longer period of time as compared to liquid formulations. © 2010 Elsevier B.V.